2015
DOI: 10.3923/ijp.2015.874.887
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Medicinal Herbs for the Management of Diabetes and its Complications: An Evidence-Based Review

Abstract: A B S T R A C T Diabetes mellitus is a complex metabolic disease associated with impaired insulin secretion, developing insulin resistance as well as β-cell dysfunction, that leads to abnormal glucose, protein and lipid metabolism, inflammatory responses and oxidative damages. Traditional medicines suggest a wide range of remedies for the management of symptomatologies associated with chronic disorders including diabetes mellitus. The aim of the present study is to elicit the most popular traditionally used me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 100 publications
2
20
0
Order By: Relevance
“…In recent years, the rapid development of high-throughput sequencing technology provides a new way to better understand the gut microbiota. T2DM is a complex of metabolic disorders, including lipid, protein, and carbohydrate metabolic abnormalities [2]. Previous and present studies demonstrated that 7-week oral administration of BDB significantly decreased the blood glucose levels, suggesting an anti-diabetes effect.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In recent years, the rapid development of high-throughput sequencing technology provides a new way to better understand the gut microbiota. T2DM is a complex of metabolic disorders, including lipid, protein, and carbohydrate metabolic abnormalities [2]. Previous and present studies demonstrated that 7-week oral administration of BDB significantly decreased the blood glucose levels, suggesting an anti-diabetes effect.…”
Section: Discussionsupporting
confidence: 56%
“…Type 2 diabetes mellitus (T2DM), which is the most common type of diabetes, is characterized by insulin resistance, insulin deficiency, or β-cell failure [1,2]. The development and occurrence of T2DM are mostly related to obesity, family history, and diet [3].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products derived from medicinal plants play an important role as useful tools in pharmacological studies in the management of diabetes mellitus (Farzaei et al, 2015). Researchers have proved that the antidiabetic activity of medicinal plants is due to the presence of phenolic compounds, flavonoids, terpenoids, coumarins and other ingredients which demonstrate hypoglycaemic activity (Aswathy and Jessykutty, 2017).…”
Section: Traditional Herbal Medicines For the Management Of Diabetes mentioning
confidence: 99%
“…The conventional therapeutic options for treatment of DM exhibit insufficient efficacy and can result in several adverse effects including weight gain, hypoglycemia, as well as liver and kidney toxicity. Therefore, discovering new hypoglycemic agents with few side effects and desired potency is necessary to counteract insulin resistance (Farzaei, Morovati, Farjadmand, & Farzaei, 2017; Farzaei, Rahimi, Farzaei, & Abdollahi, 2015).…”
Section: Introductionmentioning
confidence: 99%